Striving to Be 'Clearly Open' and 'Crystal Clear' : Monetary Policy Communication of the CNB - Bulir, Ales (IMF Working Papers; Working Paper ;, 2008)
The Czech National Bank has a respectable track record in terms of its policy actions and the corresponding inflation outturns. Using a simple forward-looking policy rule, we find that its main communication tools-inflation targets, inflation forecasts, verbal assessments of the inflation risks contained in quarterly inflation reports, and the voting within the CNB Board-provided a clear message in about three out of every four observations in our 2001- 2005 sample.